2019
DOI: 10.1111/eva.12794
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genomics to the rescue of a tropical bee threatened by habitat loss and climate change

Abstract: Habitat degradation and climate change are currently threatening wild pollinators, compromising their ability to provide pollination services to wild and cultivated plants. Landscape genomics offers powerful tools to assess the influence of landscape modifications on genetic diversity and functional connectivity, and to identify adaptations to local environmental conditions that could facilitate future bee survival. Here, we assessed range‐wide patterns of genetic structure, genetic diversity, gene flow, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 88 publications
(142 reference statements)
2
44
1
2
Order By: Relevance
“…IBD was based on geographic distance. However, instead of using the Euclidian distance among population pairs, we created a raster by assigning a 0.5 value to all 1-km 2 pixels [90,91] of the Iberian Peninsula map. We then calculated pairwise distances, known as geographic resistance distance, among all A. thaliana populations employing the new raster.…”
Section: Drivers Of Genetic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…IBD was based on geographic distance. However, instead of using the Euclidian distance among population pairs, we created a raster by assigning a 0.5 value to all 1-km 2 pixels [90,91] of the Iberian Peninsula map. We then calculated pairwise distances, known as geographic resistance distance, among all A. thaliana populations employing the new raster.…”
Section: Drivers Of Genetic Differentiationmentioning
confidence: 99%
“…Given the inherent spatial dependence structure in pairwise comparisons between A. thaliana populations, all MLPE considered spatial locations. To this end, we used a modification of the MLPE model incorporating the correlation between pairwise measurements due to comparison of populations and spatial locations (nested MLPE or NMLPE) [91]. Since the independent variables (IBD, IBE and IBR) used in NMLPE had very different units, we normalized them by subtracting the mean and dividing by the standard deviation in all analyses.…”
Section: Drivers Of Genetic Differentiationmentioning
confidence: 99%
“…In this case, we assigned developed land, cultivated land, and forest habitats a resistance value of 0.1 and all other land cover types within the study area a value of 0.9. Finally, we tested a set of hypotheses (Set C) that single land uses are independently driving gene flow, with each of the land‐use types in Hypothesis B as single terms, with each assigned a resistance value of 0.1, and all other land‐use types assigned a resistance value of 0.9 (Jaffé et al., 2019; as per Jha, 2015). To test for any nonlinear relationships between genetic distance and land use, we also created three additional resistance maps per hypothesis, varying the low and high resistance values between 0.1–0.3 and 0.5–0.9, respectively (sensu Jha & Kremen, 2013b; Ortego, Aguirre, Noguerales, & Cordero, 2015; Zellmer & Knowles, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Explanatory variables met normality assumptions and were not transformed, but they were scaled prior to modeling. We conducted a test for residual spatial autocorrelation for the full MLPE model for each type of metrics (Jaffé et al, 2019) and found no significant autocorrelation. Because the same sampling sites were considered in each submodel, this satisfies the spatial independence assumption for all submodels, i.e., model selection with subsets of the predictors included in the full model.…”
Section: Statistical Modelingmentioning
confidence: 99%